Fabrication and characterisation of alumina-nickel composites - Gan, Abel (Nanyang Technological University, 2024)
Bioinspired materials draw upon the structures and processes observed in living organisms, including plants, animals, and microorganisms, to develop materials that possess distinct characteristics. This type of material typically possesses remarkable properties such as being lightweight, combined with exceptional strength and toughness which allows for application across diverse fields such as engineering, medicine, and environmental conservation. However, replicating bioinspired materials has posed significant challenges. While several successful attempts have been made to mimic their structural and mechanical features, these efforts typically involve demanding considerable energy input and are often constrained by various limitations. In this study, the objective is to replicate and fabricate one of these natural materials known as Nacre. The goal is to create a nacre-inspired composite consisting of ceramics and metals using magnetically assisted slip casting. By varying the initial conditions before and during the fabrication process, this study aims to understand the effects of these conditions on the microstructure and in the process identify the optimal conditions and parameters to obtain a composite with desirable quality. This processing methodology holds promise for generating lightweight synthetic materials possessing enhanced strength and toughness. Such a material obtained by this fabrication technique could find its way into industries such as construction, aerospace, and marine among many others.